A Clinical Study of Allergic Contact Dermatitis (TAJ: Journal of Teachers Association, 2009)
This study was done in the outpatient department of Rajshahi Medical College Hospital from April 2005 to March 2006. In this study the clinical patterns of allergic contact dermatitis and their causative allergic products was studied. Out of 50 patients, 34(68%) were female and 16(32%) were male. The study shows that the clinical patterns of allergic contact dermatitis are eczema 24(48%), hyperpigmentation 14(28%), urticaria 6(12%), acneform eruption 04(08%) and hypopigmentation 02(04%). Allergic products causing allergic contact dermatitis was cosmetics 20(40%), shoe 08(16%), clothing 06(12%), occupation 05(10%) adhesive 04(08%), metals & metal salts 04(08%) topical drugs 02(04%) and rubber gloves 01(02%).   doi: 10.3329/taj.v19i2.3151 TAJ 2006; 19(2): 60-62